HOLOCENE VARIABILITY OF BOTTOM WATER HYDROGRAPHY ON THE KARA SEA SHELF (SIBERIA) DEPICTED IN MULTIPLE SINGLE-VALVE ANALYSES OF STABLE ISOTOPES IN OSTRACODS - Simstich J.; Bauch D.; Spielhagen R.F.; Stanovoy V.; Erlenkeuser H. (My University, 2004)
Ostracods secrete their valve calcite within a few hours or days, therefore, its isotopic composition records ambient environmental conditions of only a short time span. Hydrographic changes between the calcification of individuals lead to a corresponding range (max.–min.) in the isotope values when measuring several (≥5) single valves from a specific sediment sample. Analyses of living (stained) ostracods from the Kara Sea sediment surface revealed high ranges of >2‰ of δ18O and δ13C at low absolute levels (δ18O: <3‰, δ13C: <−3‰) near the river estuaries of Ob and Yenisei and low ranges of ∼1‰ at higher absolute levels (δ18O: 2–5.4‰, δ13C: −3‰ to −1.5‰) on the shelf and in submarine paleo-river channels. Comparison with a hydrographic data base and isotope measurements of bottom water samples shows that the average and the span of the ostracod-based isotope ranges closely mirror the long-term means and variabilities (standard deviation) of bottom water temperature and salinity. The bottom hydrography in the southern part of the Kara Sea shows strong response to the river discharge and its extreme seasonal and interannual variability. Less variable hydrographic conditions are indicative for deeper shelf areas to the north, but also for areas near the river estuaries along submarine paleo-river channels, which act as corridors for southward flowing cold and saline bottom water.
Keywords: Kara Sea; Ostracoda; stable isotopes; annual variations; bottom water; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен